Stability and Toxicity Test of Angkak Pigment Powder from Sago Hampas- Rice Flour Substrate as Natural Dyes - Dian Pramana Putra; Novelina Novelina; Alfi Asben (Green Engineering Society, 2021)
Sago hampas is waste from processing sago starch. Sago hampas is generally thrown away without any further treatment. Sago hampas contain nutrients that can be used as a substrate for fermentation of angkak. The study aims to determine the stability and toxicity of angkak pigment powder from sago hampas-rice flour substrate. The study used exploratory research design through experiments in the laboratory. This study used the UV-vis spectrophotometer method in observing the stability of the Angkak powder pigment and the brine shrimps method of angkak pigment powder toxicity test. The results showed that the level of solubility of angkak pigment powder will increase at higher temperatures. Stability of angkak pigment powder tends to decrease with longer heating, the higher of heating temperature and the longer of irradiation. Angkak pigment powder are more stable at neutral and alkaline pH compared with acidic pH. And it is not toxic to experimental animals with LC50 value of angkak pigment powder of 2,897.05 ppm. The conclusion of this study is that temperature affects the intensity of the angkak pigment. Angkak is unstable along with heating time, heating temperature and longer of irradiation.